Ecological Soil-Cement Bricks from Waste Materials - Acchar, Wilson; Marques, Sheyla K. J. (SpringerBriefs in Applied Sciences and Technology,, 2016)
This book proposes the use of waste from oil drilling and sugar cane bagasse ash in the production of ecologically friendly soil-cement bricks. It offers a viable alternative to the traditional bricks available on the market, which use wood as fuel: manufacturing bricks from waste is less costly and does not require the consumption of trees and forests. It also proposes an alternative to the current discharging of the above-mentioned types of waste in sanitary landfills, avoiding additional environmental problems.